Pulmonary oxygen uptake on‐kinetics can predict acute physiological responses to resistance exercise training in healthy young men. (29th May 2019) - Kubo, Yusuke; Fujita, Daisuke; Sugiyama, Shuhei; Hosokawa, Masato; Nishida, Yusuke
Summary: Purpose: To clarify whether pulmonary oxygen uptake kinetics ( τ V ˙ O 2 p ) at the onset of moderate‐intensity exercise can predict acute physiological responses to resistance exercise training (RET). Methods: We investigated the relationship between τ V ˙ O 2 p and acute metabolic and hemodynamic responses to a single RET session in 27 healthy young adult men. Cardiopulmonary exercise was on a cycle ergometer, and a single RET at 30% or 60% of one‐repetition maximum was on a bilateral leg‐extension machine. We measured the anaerobic threshold, peak V ˙ O 2 and τ V ˙ O 2 p while cardiopulmonary exercising, and the rates of increase in blood lactate (Bla), heart rate (HR), systolic blood pressure (SBP) and rate pressure product (RPP) for a single RET. Results: There were significant positive associations between τ V ˙ O 2 p and the rates of increase in Bla, HR, SBP and RPP during a single RET session ( P <0·05). However, the anaerobic threshold and peak V ˙ O 2 did not significantly affect these parameters. Conclusion: The τ V ˙ O 2 p is a useful evaluation index for predicting acute physiological responses to RET.